2023
DOI: 10.1111/jcmm.17940
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial drug discovery against malaria parasites through haplopine modification: An advanced computational approach

Shopnil Akash,
Guendouzi Abdelkrim,
Imren Bayil
et al.

Abstract: The widespread emergence of antimalarial drug resistance has created a major threat to public health. Malaria is a life‐threatening infectious disease caused by Plasmodium spp., which includes Apicoplast DNA polymerase and Plasmodium falciparum cysteine protease falcipain‐2. These components play a critical role in their life cycle and metabolic pathway, and are involved in the breakdown of erythrocyte hemoglobin in the host, making them promising targets for anti‐malarial drug design. Our current study has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…They have the highest score against the Angiotensin II receptor of any investigated ligand due to two more hydrogen bonds with residues Arg67, Tyr87, and Cys180, among other considerations. Moreover, hydrogen bonds predominated, indicating that the compounds interacted strongly with the receptor. , In particular, this is the first time that the docking interaction between these naturally occurring substances and the Angiotensin II receptor to accomplish the aforementioned biological activity as an antihypertensive has been identified.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…They have the highest score against the Angiotensin II receptor of any investigated ligand due to two more hydrogen bonds with residues Arg67, Tyr87, and Cys180, among other considerations. Moreover, hydrogen bonds predominated, indicating that the compounds interacted strongly with the receptor. , In particular, this is the first time that the docking interaction between these naturally occurring substances and the Angiotensin II receptor to accomplish the aforementioned biological activity as an antihypertensive has been identified.…”
Section: Resultsmentioning
confidence: 86%
“…Moreover, hydrogen bonds predominated, indicating that the compounds interacted strongly with the receptor. 42,43 In particular, this is the first time that the docking interaction between these naturally occurring substances and the Angiotensin II receptor to accomplish the aforementioned biological activity as an antihypertensive has been identified.…”
Section: Pre-admet and Pretoxicitymentioning
confidence: 96%
“…For example, the arrangement, substitution, and total number of hydroxyl groups significantly influence numerous mechanisms of antioxidant activity, including the ability to scavenge free radicals and chelate metal ions ( Ul Islam et al, 2021 ). Flavonoids have shown strong anticancer properties against different components in the PI3K/Akt/mTOR pathway ( Rehan et al, 2020 ; Zughaibi et al, 2021 ; Akash et al, 2023 ; AlZahrani et al, 2023 ). The scientific evidence supports the use of flavonoids as an adjuvant in radiation and other conventional therapeutic medications, in addition to their possible use as therapeutic agents against various cancers ( Ahmad et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…These activities are probably brought on by the presence of -N-H, –C S, groups [ [10] , [11] , [12] , [13] , [14] , [15] ]. Ahamad et al reported a new class of metal chelated polyurea for its excellent antimicrobial activity against S. aureus, E. coli, B. subtilis , and S. typhi [ [16] , [17] , [18] , [19] , [20] ]. Azo series based on transition metal complexes (Cu 2+ , Zn 2+ , Mn 2+ , Co 2+ and Ni 2+ ) were screened for their antibacterial and antifungal activities against S. aureus, E. coli and A. niger and C. albicans [ 21 ].…”
Section: Introductionmentioning
confidence: 99%